Comment on R. P. Byron's "The Restricted Aitken Estimation of Sets of Demand Relations" - Basmann, R. L.; Battalio, R. C.; Kagel, J. H. (Econometrica, 1973)
that the latter system fits only poorly, Byron went on to speculate (in the presence of those data) whether any system of demand functions would fit any relevant empirical data as well. The system of demand functions Byron said he intended to test and estimate belongs to the class Y'O of systems of real-valued functions of real variables that are characterized by (la) xi = AiME H p' (i=1 . ,m) j=1 and m